Firm Responses and Wage Effects of Foreign Demand Shocks with Fixed Labor Costs and Monopsony - Dhyne, Emmanuel; Kikkawa, Ayumu Ken; Komatsu, Toshiaki; Mogstad, Magne; Tintelnot, Felix (American Economic Review, 2025)
We quantify the firm responses and real wage effects of foreign demand shocks. We use Belgian microdata to construct firm-specific measures of demand shocks, which capture that firms pass on foreign demand shocks to domestic suppliers. Our estimates of firm responses to these shocks suggest that firms face upward-sloping labor supply curves and have sizable fixed labor costs. We specify a general equilibrium model with these features to quantify the aggregate effects of simulated tariff shocks on wages. We find that ignoring fixed labor costs substantially underestimates aggregate effects on wages, whereas incorporating upward-sloping labor supply appears less consequential. (JEL D22, F13, F16, J22, J31, J42, L25)